The Effect of Katuk (Sauropus androgunus (L) Merr) Leaf Biscuit on Increasing Prolactine Levels of Breastfeeding Mother - Indrayani, Diyan; Shahib, Muhamad Nurhalim; Husin, Farid (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Prolactin is one of the important hormones for increasing the synthesis and secretion of breast milk. Katuk (Sauropus androgunus (L) Merr) leaf biscuits are standardized and practical processed food products that are substituted with katuk leaf extract and have met the requirements as additional food for breastfeeding mothers. In addition to nutritional content, katuk leaf biscuits also contain phytochemical compounds, namely steroids and alkaloids. The purpose of this study was to determine the effect of katuk leaf biscuits on increasing serum prolactin levels of breastfeeding mothers. This research was conducted in the city of Bandung. The design used was a randomized controlled trial. The sample was 45 primiparous postpartum mothers who gave birth at the public health center for Obstetrics and Neonatal Basic Emergency Services (Puskesmas PONED) in Bandung City, consisting of 22 treatment groups and 23 control groups. Sampling is conducted by block randomization. Data were analyzed using the Independent T-test. The results showed that there was an effect of katuk leaf biscuits on increasing serum prolactin levels in breastfeeding mothers. It is suggested that katuk leaf biscuits be used as an alternative as an effort to increase breast milk production so that it can support the success of exclusive breastfeeding.